IgG subclasses identification of immunized mice sera with Dengue tetravalent DNA vaccine based on prM-E genes: Identifikasi Subkelas IgG Dari Mencit yang Diimunisasi dengan Kandidat Vaksin DNA Dengue Tetravalent - Beti Ernawati Dewi; Rizka Andhitia Mentari Putri; Tjahjani Mirawati Sudiro; Fitriyah Sjahta (Indonesian Society for microbiology, 2022)
Background: Dengue fever is still a serious health problem in the world. DENV consists of 11 kb of single positive-stranded RNA encoding three structural proteins and seven non-structural proteins. PrM and E proteins are the main targets of the antibody response that rich of epitopes and able to induce protective immunity. There are four DENV serotypes that have similar antigenic structures in the amino acid sequence of protein E. In our previous study, we successfully constructed a recombinant tetravalent DNA vaccine candidate consisting pUMVC4a-based expression plasmid for prM-E protein of all DENV serotypes (pUMD1, pUMD2, pUMD3 and pUMD4). It has been proved that the vaccine candidate was able to induced anti-dengue IgG as well as neutralization antibody to all DENV serotypes. This study aims to determine IgG subclasses of immunized mice with recombinant tetravalent DNA vaccine candidates based on prM-E genes of all serotypes. Methods: Mice (Balb/c) were immunized with a dose of 100 Î¼g 100 uL/mouse in triplicate, at three weeks interval. Blood was drawn two weeks post immunization as well as termination blood. IgG subclasses titre were measured using in-house indirect ELISA. Results: The titer of IgG2a subclass was the highest levels with optical density of 1.004Â±0.154 followed by IgG1,IgG2b, and IgG3 to DENV-2, respectively. Conclusion: The data demonstrate the humoral immune response IgG subclasses of this recombinant tetravalent DNA vaccine candidates based on prM-E genes of all serotypes, supporting further translational studies to advance the development of this candidate in response to DENV infection. Keywords: dengue vaccine, DNA vaccine, recombinant, IgG subclass, Tetravalent